Upaya Pengembangan Produk Unggulan Desa melalui Pelatihan Pengolahan Susu di Desa Ciporeat: Efforts to Development of Village Superior Products through Milk Processing Training in Ciporeat Village - Utan Sahiro Ritonga; Hadi Yusuf Faturochman; Sutadi Triputra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Mozzarella cheese and yogurt are dairy products that are popular in the community. However, not many people know how to make these products, so training is needed to improve community skills in making mozzarella cheese and yogurt for business opportunities for the community. The training was conducted on PKK member in Ciporeat Village, Cilengkrang District, Bandung Region. The method of implementing the activity includes pre-test, presenting material, practice of making mozzarella and yogurt and posttest. Participants were very enthusiastic in participating in the training activities and gave positive responses to these activities. The activity can increase the knowledge and skills of the community in training milk into mozzarella cheese and yogurt. At the time of the pre-test, people's knowledge of products, tools and materials and how to process mozzarella cheese and yogurt products was very low, after training there was an increase in knowledge of products, tools and materials, as well as how to process mozzarella cheese and yogurt products to reach 100%.